2019
DOI: 10.3389/fendo.2019.00455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Modification and Anti-diabetic Medicine on Prediabetes Progress: A Systematic Review and Meta-Analysis

Abstract: Background: Pre-diabetes is a risk factor for full-blown diabetes; it presents opportunities to prevent the actual diseases. It is therefore essential to identify effective preventive strategies, and to clarify the direction of future research. Methods: PubMed, Embase and Cochrane Central Register of Controlled Trials were searched using key terms ( Supplementary Table 1 ). We applied network meta-analysis to multiple comparisons among various diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
1
20
0
3
Order By: Relevance
“…Multivariable linear regression analyses showed that the intervention has high difference of differences in LDL, Triglycerides, T.Cholestrol and fasting blood sugar (FBS). A similar positive effect of life style modi cation was reported on lipid pro les (40)(41) and blood sugar level (42). It was also observed that the difference in differences was lower by 30.5 mg/dl for LDL among males compared to females.…”
Section: Discussionsupporting
confidence: 75%
“…Multivariable linear regression analyses showed that the intervention has high difference of differences in LDL, Triglycerides, T.Cholestrol and fasting blood sugar (FBS). A similar positive effect of life style modi cation was reported on lipid pro les (40)(41) and blood sugar level (42). It was also observed that the difference in differences was lower by 30.5 mg/dl for LDL among males compared to females.…”
Section: Discussionsupporting
confidence: 75%
“…It is known that IFG is pre-diabetes [19] , and the prevalence of IFG in this study was 11.95%, which is slightly lower than diabetes mellitus. If they are not taken seriously, it is easy for them to further develop into diabetes, which in turn increases the prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 57%
“…73 Also Sheng et al found that long-term modifications in lifestyle including nutrition, exercise and weight loss contribute to health by reducing fasting, and 2-h postprandial blood glucose, total cholesterol and by increasing HDL. 74 Our study had some strengths, to the best of our knowledge, this is the first study to investigate the association between healthy lifestyle score including four factors together (diet, physical activity, smoking status and BMI) with both CRF and muscle strength and in order to reduce bias risk we used the standard protocols for assessment of CRF, hand grip strength, dietary intake and physical activity. In addition, we adjusted for several known factors which may influence CRF and muscle strength also the sample covered a wide age range.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chitra et al investigated that diet and physical activity significantly affect the serum lipid profile 73 . Also Sheng et al found that long‐term modifications in lifestyle including nutrition, exercise and weight loss contribute to health by reducing fasting, and 2‐h postprandial blood glucose, total cholesterol and by increasing HDL 74 …”
Section: Discussionmentioning
confidence: 99%